Studi Komparasi Pemikiran Thomas Lickona Dan Abdullah Nashih Ulwan Tentang Pendidikan Karakter Keluarga Dan Sekolah - Ahsani, Muhammad (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2014)
In addition to having the same concept of the importance of family and schoolin shaping the character, Thomas Lickona and AbdullÄ Nas á¸¥ hih UlwÄ n alsohave different thoughts and concepts theoretically and practically. AccordingLickona, the important values that should be developed in character educationamong others, include the value of the trust, trustworthy (trusworthines), respect,responsibility, fairness both t o themselves and others, caring, honesty, andcitizenship. On the otherhand, â€˜AbdullÄ Nas á¸¥ hih UlwÄ n provide a completeguide for the realization of perfect parenting. In addition to referring to the textsof the Qurâ€™an and Hadith shohih , he also equip it with scientific and rationalevidences. In his discussion UlwÄ n not only reveal how education should be basedupon the phases of growth, but he is more general ranging from how to educatechildren from birth until the age of school. The approach that the researcher usedin this study is descriptive qualitative approach with critical analysis.Key words: Thomas Lickona, Abdu l lÄ Nas á¸¥ hih UlwÄ n, CharacterEducation